2019
DOI: 10.17524/repec.v13i4.2295
|View full text |Cite
|
Sign up to set email alerts
|

Efeitos do Compartilhamento de Informações no Risco e Desempenho da Aliança Estratégica de Cooperativas

Abstract: Objetivo: Este estudo analisa os efeitos do compartilhamento de informações no risco e desempenho da aliança estratégica de cooperativas, mediado pelo compartilhamento de conhecimento e vazamento de informações. Método: Pesquisa de levantamento foi realizada em cooperativas agropecuárias listadas na Organização das Cooperativas Brasileiras (OCB) com gestores (gerente, supervisor, coordenador e controller) cadastrados na rede LinkedIn. O questionário foi enviado pela plataforma SurveyMonkey aos 516 gestor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 29 publications
(80 reference statements)
0
4
0
3
Order By: Relevance
“…This result differs from what was presented in the studies of Keers and Van Fenema (2018), Soper et al (2007), and Trkman and Desouza (2012), who found effects of risk management on knowledge sharing, that is, that managing this sharing avoids breaches and inappropriate or irrelevant sharing. Beuren et al (2019) observed that information breaches are directly associated with the risk of the alliance. One possible explanation for the findings of the research may be that these organizations do not perceive risks in knowledge sharing, but instead see sharing as something natural in the cooperation between the parties.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…This result differs from what was presented in the studies of Keers and Van Fenema (2018), Soper et al (2007), and Trkman and Desouza (2012), who found effects of risk management on knowledge sharing, that is, that managing this sharing avoids breaches and inappropriate or irrelevant sharing. Beuren et al (2019) observed that information breaches are directly associated with the risk of the alliance. One possible explanation for the findings of the research may be that these organizations do not perceive risks in knowledge sharing, but instead see sharing as something natural in the cooperation between the parties.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Risk management involves the organized and economic application of resources to mitigate the probability of the impact of negative events or to enhance opportunities (Hubbard, 2020). Kritzman (2000) and Beuren et al (2019) warn that some risks assume more important characteristics in the context of cooperativism, due to the data, information, and knowledge that can cause uncertainties, which points to the need to carry out risk management. According to Zsidisin et al (2000) and Beuren et al (2019), the constant verification of risks surrounds the communication and analysis of information that contributes to suitable risk management strategies.…”
Section: Cooperative Behavior and Risk Managementmentioning
confidence: 99%
See 2 more Smart Citations
“…De um lado, o compartilhamento de informações, consubstanciado em características como qualidade, confiabilidade e precisão da informação (Moores & Yuen, 2001), fornece suporte para melhorar o processo decisório dos envolvidos, o que não ocorre quando há limitações na troca de informações (Treurniet & Wolbers, 2021). De outro lado, melhorias no processo decisório favorecem o compartilhamento de informações, o que proporciona condições para melhorar o desempenho organizacional (Beuren et al, 2020;Yang & Maxwell, 2011).…”
Section: Introductionunclassified